JENIS PAKAN KUKANG JAWA (Nycticebus javanicus) DI TAMAN WISATA ALAM GUNUNG TAMPOMAS - Rendi Nurhadi; Asep Purwanto (Fakultas Kehutanan Universitas Winaya Mukti, 2020)
Nycticebus javanicus is one of endemic species of Java island that one of endangered species. Data and research of Nycticebus javanicus is still low. So, this condition difficult to it conservation. Existing of Nycticebus javanicus depend on forest vegetation including food tree. The method of research by plot of tree food observation, niche analysis that focus of feeding activity and part of feed. The result of research are 17 species of tree, there are aren (Arenga pinnata), bamboo (Bambusa vulgaris), bisoro (Ficus leificarva), hamirung (Vernonia arborea), huru leueur (Phoebe excelsa), kaliandra (Calliandra calotyrsus), kiteja (Parinari sumatrana), kitembaga (Eugenia cuprea), kibanen (Criyteronia paniculata), kiara (Ficus altisima), kipait (Tithonia diversifolia), kisampang (Evodia latifolia), kilaki (Adina fagifolia), nangsi (Villebrunea rubescens), sempur (Dillenia indica), teureup (Artocarpus elastic), and tangkil (Gnetum gnenom). Part of feed is fruit, leef, sprout, and flower.